Knowledge management: Implications to SMEs performance in Nigeria - Nuel, Okoli Ifeanyi Emmanuel; Peace, Nwakoby Nkiru; Ifechi, Adani Nnenne (Nurture, 2023)
Purpose: The purpose of this research is to determine the effect of knowledge management on firm’s performance in selected manufacturing small and medium enterprises (SMEs) in Southeast Nigeria. Design/Methodology/Approach: The data is gathered from different manufacturing SMEs in Southeast Nigeria for this study. The sample size was 196 gathered from the population size of 800 selected manufacturing SMEs. The convenience sampling is used for the study. Descriptive statistics (frequency tables and percentages) was adopted for data presentation, however, Pearson correlation co-efficient along with regression analysis was applied for hypotheses testing. Results: The results exposed that there is an encouraging positive significant association between knowledge management along with SMEs performance. The outcome expressed that there is an encouraging significant relationship between the knowledge management dimensions (knowledge sharing, knowledge acquisition in addition to knowledge protection) and firm performance dimensions (market share, sales growth as well as customer satisfaction). Conclusion: The study concluded that SMEs which acquire new knowledge tend to satisfy their customers more than those with outdated knowledge, and those who share knowledge with employees tend to gain larger market share than those who do not share with employees. Contribution to Literature: This study contributes to the existing literature in two ways: first, this utilized the knowledge management variables which were not utilized in previous studies. Second, this study decomposed firm performance by using three different indicators.